Importance of physical fitness during the ageing process - Ruiz-Montero, Pedro Jesús; Castillo-Rodríguez, Alfonso (Sport Science, 2018)
In the world, more than 50% of 60-year-olds are obese. Obesity is a disease with serious cardiovascular risks. Obesity grows with the increasing age of a person. In addition, sedentary lifestyle causes muscle mass to decrease faster. Strength, aerobic capacity and flexibility are related to the muscle mass. Obesity and physical inactivity cause a decrease of the cognitive and functional capacity. For these reasons, ageing has a negative influence on the neuromuscular system, which increases the risk of falls in elderly people. Many researchers have recommended physical activity in which people enjoy themselves and therefore think in a way that increases their motivation. This motivation will decrease psychosocial aspects such as depression and anxiety, among others. Furthermore, physical activities should be cooperative and done in groups because this way they increase the perceptive and socio-emotional capacity of an older person. Most physical trainers and personal trainer need more information about methods and prescriptions in order to adequately carry out the training.
Keywords: ageing; physical fitness; training; health; Scopus